Aplicación de bioestimulantes foliares en dos híbridos de melon en Palmales Arenillas 2011 - Orellana Barrezueta, Freddy Arcenio (2013)
In the farm "San Vicente", located on the site Plum, 3 km from the parish of the canton Palmales Arenillas research was conducted to evaluate six products biostimulants for the content of macro, micro elements, vitamins and phytohormones., For which raised the following objectives.1. Measuring the response of hybrid cantaloupe melon and Excelsior Expedition to implementing biostimulants.2. Check the best bio-stimulant for use in type cantaloupe melon cultivars Expedition and Excelsior.3. Perform economic analysis of each treatment.The hybrids were studied genetic material Expedition and Excelsior., Pump equipment for irrigation, pressure knapsack sprayer manual, nebulizer, insecticides, fungicides, fertilizers, bio-stimulants, caliper scale.Studied six bioestimulantes two hybrids which were available 12 treatments arranged in a split plot design. With four blocks or repetitions, totaling 48 experimental units. The treatments were: Enerplant 20 g / ha; Atroestin 500 g / ha; Biozyme FT 500 ml / ha; Algaefoliar 2.0 l / ha; Enzipron 2 g / liter and Biolplus 1.0 l / ha hybrids were assigned to main plots and bioestimulantes to sub plots. The variables studied were, Pest Registration (phytosanitary problems), days to flowering, days to fruiting, days to harvest, yield: number, length, diameter and weight of fruits, Yield: Production Quality and Profitability Analysis.Statistical analyzes all variables resulted in high statistical significance for the factor B and interaction biostimulant Hybrids x biostimulants. In this context Excelsior Hybrids Expedition type and cantaloupe in the study had a phenological development similar to that reported for other melon producing areas, with similar periods to flowering, fruiting and harvesting. The length of the Agroestin fruits were superior in both hybrids, while the best average diameter reached with Enerplant 20 gr / ha. As regards the average weight, with Agrostin 500 g / ha was reached to produce fruits of 1.12 and 1.24 kilos in hybrids Excelsior and Expedition. Productivity per plant reached the highest levels of productivity with a rate of 5.8 Agroestin fruits per plant in the hybrid Excélsiur and 6.7 fruit / plant in the Expedition. Final yield of fruit per hectare, drawers, and profitability was obtained with two biostimulants, Agroestin 500 ml / ha and Algaefoliar 2.0 l / ha.